INFLUENCE OF TECHNOLOGICAL MODES OF MAGNETIC-ELECTRIC GRINDING ON MICROSTRUCTURE OF GAS-THERMAL SPRAYED NI–CR–B–SI-COATINGS - N. V. Spiridonov; M. V. Niaroda; I. O. Sokorov; A. A. Barkun (Наука и техника)
Influence of technological modes of magnetic-electric grinding on structural changes in a surface layer of gas-thermal sprayed coatings is investigated in the paper. The paper presents optimum modes of  coating roughing and finishing processes.